LITERATURE REVIEW: FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMANDIRIAN LANSIA DALAM MELAKUKAN ACTIVITY DAILY LIVING - Andriyani, Weli (Nursing Sciences Journal, 2020)
ABSTRACTBackgrounds : The increase of life expectancy affects the number and percentage of elderly population which is increasing. One of the problems which emerges from the increase of the elderly population is the increase of old dependency ratio which is influenced by various factors.Objective : The Objective of this literature review is to identify the factors related to the independence of the elderly in performing Activity Daily Living.Method : The database used includes: Google Scholar and ResearchGate. Keywords used in this article are elderly, daily activity, independence of the elderly and activities of daily living. otal of 144 articles were found from selected keywords, 129 journals were excluded because they did not fit the inclusion criteria, then 15 articles were identified, and 5 journals were excluded. Then 10 articles were finally analyzed to identify the factors related to the independence of the elderly in performing daily living activitiesResults : The results of the study factors which are related to the independence of the elderly in performing daily living activities are age, health condition, physical activity, cognitive function and family support.Conclusions and Suggestions : The dominant factors which related to the independence of the elderly in performing daily living activities is health condition factor with an OR value = 86,00. The better healt status of the elderly, the smaller the increase in dependence that supports the elderly. So that health workers can improve health education programs in the community about the elderly.